A meta-analysis of environmental factors influencing the algal colonisation in caves and rockshelters worldwide - Belda, Andrea; García-Abad, Laura; Asencio, Antonia Dolores (Acta Carsologica, 2023)
Microclimate conditions, mainly radiation, temperature and relative humidity vary according to cavities´ configurations and determine the microorganism’s colonisation. A meta-analysis was performed of environmental factors influencing the algal species colonisation in caves and rockshelters. For this purpose, the results of studies about algal colonisation in 82 caves and rockshelters in 11 European, Asian and American countries were analysed. Firstly, 412 species were counted of which Cyanobacteria predominated, followed by Chlorophyta and Bacillariophyta, and finally by Rhodophyta. The Shannon Index determined that the diversity of the algal species developing in these places was very high. The most diverse Cyanobacteria genera to appear in the different studied caves and rockshelters are Leptolyngbya with 28 different species, Gloeocapsa with 24 and Phormidium with 23. They are followed by Chroococcus with 18, Aphanothece with 14, Oscillatoria, Nostoc and Scytonema with 10 each and Schizothrix and Tolypothrix with 9 each. The most diverse Chlorophyta and Bacillariophyta genera are Chlorella with 9 different species and Diadesmis/Humidophila, Luticola and Nitzschia with 4, respectively. The principal component analysis revealed that both photosynthetically active radiation and relative humidity more actively conditioned the development of some algal species in cave environments than temperature.